Archaeology of knowledge - "Foucault, Michel" (London, 2002)
This book is emphasized on the topics of Formation of Object, Enunciative Modalities, Concepts and Strategies. It also explained the Rarity, Exteriority and Accumulation etc.
Keywords: Psychology